G20/OECD Principles of Corporate Governance (Paris, 2015)
"The G20/OECD Principles of Corporate Governance help policy makers evaluate and improve the legal, regulatory, and institutional framework for corporate governance. They also provide guidance for stock exchanges, investors, corporations, and others that have a role in the process of developing good corporate governance. First issued in 1999, the Principles have become the international benchmark in corporate governance. They have been adopted as one of the Financial Stability Board’s Key Standards for Sound Financial Systems and endorsed by the G20. This 2015 edition takes into account developments in both the financial and corporate sectors that may influence the efficiency and relevance of corporate governance policies and practices."